PP189 Filling In The Blanks: Is RWE From MAAs Used In NICE Decision Making?. (2019) - Liu, Lok Wan; Hall, Adam; Macaulay, Richard; Walsh, Sean
Abstract : Introduction: The National Institute for Health and Care Excellence (NICE) may recommend temporary funding through managed access agreements (MAAs) for oncology drugs (via the Cancer Drugs Fund [CDF]) and highly specialized therapies for rare diseases. MAAs allow for the collection of evidence to address key areas of clinical uncertainty, while providing access of medicines to patients, prior to re-appraisal by NICE. Observational data and other real-world evidence (RWE) are crucial requirements for all MAAs and herein we examine the extent these data are being used to inform HTA decisions at re-appraisal. Methods: Existing MAAs entered into between the National Health Service (NHS) England and manufacturers as of 30 October 2018 were identified; for drug:indication pairings with NICE re-appraisals, all information was reviewed and the key data extracted. Results: Of the twenty-two MAAs identified, only two drug:indication pairings have been subsequently re-appraised by NICE: BV(brentuximab vedotin):non-Hodgkin lymphoma ('recommended') and pembrolizumab:relapsed or refractory classical Hodgkin lymphoma ('recommended'). Data from a retrospective questionnaire regarding the proportion of patients that received curative stem cell transplant (SCT) post-BV (from patients who received BV in the old CDF) were accepted to provide sufficient evidence on the post-BV SCT rate by NICE. Meanwhile, for pembrolizumab, long-term survival benefit was the key clinical uncertainty; the primary data collection source was updated phase III randomized controlled trial data. At re-appraisal no reference was made to the observational data component; more mature survival data reduced uncertainty over survival benefits and were sufficient to support a positive NICE recommendation. Conclusions: Of the twenty-two MAAs to date, only two drugs have been re-appraised thus far, with both receiving positive NICE recommendations. Observational data were successfully used to address key clinical uncertainties regarding subsequent real-world treatment patterns for BV, but observational data were not referred to in the NICE recommendation for pembrolizumab. The re-appraisal of more drugs in the future will clarify the importance being placed on observational data collection requested by NICE for existing MAAs.